2011
DOI: 10.1128/jvi.01496-10
|View full text |Cite
|
Sign up to set email alerts
|

T Cell-, Interleukin-12-, and Gamma Interferon-Driven Viral Clearance in Measles Virus-Infected Brain Tissue

Abstract: Genetic studies with immunocompetent mice show the importance of both T cells and gamma interferon (IFN-␥A wide variety of RNA and DNA viruses, including measles virus (MV), West Nile virus (WNV), human immunodeficiency virus, human cytomegalovirus, herpes simplex virus type 1 (HSV-1) and HSV-2, rabies virus, poliovirus, and lymphocytic choriomeningitis virus, cross the blood-brain barrier, infect the central nervous system (CNS), and cause encephalitis in mammals (3,15,26,29,34,35,75,82,85). A suitable combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 86 publications
1
27
0
Order By: Relevance
“…The finding further underscores disparities in immune protection between the closely related flaviviruses . Overall, our results were consistent with a model of noncytolytic virus clearance from the CNS by IFN‐γ secreted from infiltrating T cells (reviewed in ), and place JEV in a heterogeneous group of neurotropic viruses that are controlled by IFN‐γ in the CNS, including Sindbis , mouse hepatitis , Theiler's murine encephalomyelitis , Borna disease , dengue and measles viruses . While our finding in mice was consistent with a reported protective role of IFN‐γ in human JE , it would be of considerable interest if noncytolytic virus clearance mediated by the cytokine also contributed to recovery from human neurotropic virus infection.…”
Section: Discussionsupporting
confidence: 90%
“…The finding further underscores disparities in immune protection between the closely related flaviviruses . Overall, our results were consistent with a model of noncytolytic virus clearance from the CNS by IFN‐γ secreted from infiltrating T cells (reviewed in ), and place JEV in a heterogeneous group of neurotropic viruses that are controlled by IFN‐γ in the CNS, including Sindbis , mouse hepatitis , Theiler's murine encephalomyelitis , Borna disease , dengue and measles viruses . While our finding in mice was consistent with a reported protective role of IFN‐γ in human JE , it would be of considerable interest if noncytolytic virus clearance mediated by the cytokine also contributed to recovery from human neurotropic virus infection.…”
Section: Discussionsupporting
confidence: 90%
“…The products of these genes may play a critical role in inhibition of viral spread into non-infected cells and interference of viral replication in the infected cells [44]. IFNγ, on the other hand, is known to mediate its effect via the JAK-STAT signaling pathway leading to the subsequent activation of macrophages and NK cells, and expression of specific major histocompatibility complex proteins [45,46]. A study by Zhou et al [47] showed that infection of human monocyte-derived macrophages with MERS-CoV induced the expression of IFN-γ and the subsequent expression of major histocompatibility complex class-I genes [47].…”
Section: Discussionmentioning
confidence: 99%
“…T cells reduce the susceptibility of mice to many CNS viral infections such as measles and West Nile virus; 47, 48, 49, 50, 51 however, T-cell-mediated damage to the CNS has been described in LCMV and BDV. 52,46 The studies presented here show that TCRV infection in T-cell sufficient animals results in significant infiltration of T cells and monocytes into the parenchyma of the CNS, while T-cell-deficient mice (CD3ɛ KO) develop only a mild inflammation with marginal increases in the expression of chemokines and proinflammatory cytokines (Figure 3aii).…”
Section: Discussionmentioning
confidence: 99%